Draft Tenth Five Year Plan 2002-2007 and Annual Plan 2002-2003 Vol-I Government of Madhya Pradesh - Planning Commission (Planning Commission, 2002)
On re-organisation of States, the State of Madhya Pradesh was formed on November 1, 1956 comprising the seventeen districts of Mahakoshal, two districts of Bhopal, the eight districts of Vindhya Pradesh, sixteen districts of Madhya Bharat, except the Sunel enclave of Mandsaur district, which was included in Rajasthan, and the Sironj sub-division of the Kotah district of Rajasthan. At the time of its formation, the state had 43 districts. Subsequently two large districts were bifurcated. Sixteen more districts were formed in the year 1998.
Government of Madhya Pradesh, Planning, Economics and Statistics Department